A radical hydrohaloalkylation of the ligand sphere of a chiral dehydroalanine Ni(II) complex: An asymmetric route to halogenated α-amino acid derivatives - Nadezhda V. Stoletova; Alexander F. Smol'yakov; Andrey A. Tyutyunov; Victor I. Maleev; Vladimir A. Larionov (Tetrahedron Chem)
An asymmetric synthetic protocol for the access to chiral artificial halogenated α-amino acid (α-AA) derivatives was elaborated through the radical functionalization of a double bond in the ligand sphere of a robust chiral dehydroalanine Belokon's Ni(II) complex by hydrohaloalkylation reaction. A 4-cyano-pyrydine/B2Pin2 system promoted the in situ generation of radicals from halocarbons (including the hetero halogen atoms) for the subsequent coupling with the Ni(II) complex, providing the desired complexes with the yields in the range of 40–65%. The further post-modification of the side AA chain allowed to obtain the complexes with cyclopropane ring and to substitute the bromine atom on hydrogen one as well. Exemplary, two enantiopure α-AAs, including (S)-2-amino-4,4,4-trichlorobutanoic acid, were isolated by an acidic decomposition of the single diastereomeric Ni(II) complexes along with the recovery of the chiral auxiliary.